Concepts of power in boundary spanning research: A review and research agenda - Isabel Collien (International Journal of Management Reviews, 2021)
This meta-analytic review of power-sensitive boundary spanning research provides strong evidence that power enables, broadens and limits boundary spanning practices and outcomes. Boundary spanners use power bases to drive innovation and empower others to maintain cross-cultural collaboration, while altering unequal power relations that hinder learning and knowledge-sharing in organizations. The review further points to avenues for future research on power in boundary spanning processes: future boundary spanning studies would profit from strengthening a relational, social-constructivist understanding of power bases. This encompasses accounting for the power bases of all actors involved, expanding the notion of power bases to demographic diversity of gender, race or class, or showing how the relative importance of power bases is constructed within fields. Boundary spanning research would also benefit from expanding postcolonial and poststructuralist perspectives, which provide tools to detect subtle workings of power in boundary spanning processes. This may alter theoretical and practical implications, for example when boundary objects associated with transparency and freedom may be presented as limiting boundary spanners' field of action.
Keywords: 650